Porous atomizing core capable of releasing negative ions and its manufacturing method

The porous atomization core, enriched with tourmaline and other materials, addresses the challenges of bacterial growth and environmental concerns by releasing negative ions and far infrared radiation, enhancing atomization efficiency and extending the core's lifespan.

JP7655589B2Active Publication Date: 2025-04-02SHENZHEN HUACHENGDA PRECISION INDUSTRY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023572087
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-04
Filing Date
2021-11-29
Publication Date
2025-04-02
Estimated Expiration
2041-11-29

AI Technical Summary

Technical Problem

Existing atomization cores face challenges in maintaining long-term atomization efficiency and longevity due to bacterial growth and limited environmental friendliness, particularly in e-cigarette and medical applications.

Method used

A porous atomization core is developed using a composition that includes 50 to 90 parts of tourmaline, along with ceramic powder, pore-forming agents, and other additives, which is capable of releasing negative ions and far infrared radiation, thereby enhancing atomization efficiency and extending the core's lifespan.

Benefits of technology

The use of tourmaline and other additives in the atomization core effectively decomposes harmful gases, promotes bioelectric phenomena, and extends the core's usability while ensuring environmental friendliness and improved health benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655589000002
    Figure 0007655589000002
  • Figure 0007655589000003
    Figure 0007655589000003
  • Figure 0007655589000001
    Figure 0007655589000001
Patent Text Reader

Abstract

The present invention discloses a porous atomizing core capable of releasing negative ions and a method for producing the same. The porous atomizing core includes, as raw materials and their mass parts, 50-90 parts of tourmaline, 0-30 parts of ceramic powder, 10-30 parts of pore former, 0-30 parts of combustion improver, 0-35 parts of paraffin, and 0-2 parts of surfactant. The ceramic powder includes at least one of negative ion powder, far infrared powder, attapulgite, feldspar, and zeolite. The porous atomizing core capable of releasing negative ions in the present invention uses tourmaline as one of the raw materials, and decomposes and removes harmful gases in the atomizing liquid and air by utilizing its pyroelectricity, piezoelectricity, infrared radiation, negative oxygen ion emission, and bioelectricity properties. This makes the porous atomizing core environmentally friendly and has excellent atomizing effect, thereby satisfying people's pursuit of health products and extending the expiration date of the atomizing core.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of atomization, and in particular to a porous atomization core capable of releasing negative ions and a method for manufacturing the same. [Background technology]

[0002] As the atomization industry continues to develop, the use of porous atomization cores has gradually become a part of people's lives. However, due to the different fields of use and the diversity of atomization liquids, general atomization cores cannot guarantee long-term atomization, and the occurrence of bacteria due to the expiration of atomization liquids will also greatly shorten the service life of the atomizer. This is especially true in the industries of electronic cigarette atomization and medical atomization. Moreover, with people's relentless pursuit of health ideals, it seems that it is particularly important to research healthy and environmentally friendly atomization cores.

[0003] Currently, one of the solutions is to choose environmentally friendly materials and replace the atomizing core periodically, but this not only greatly limits the scope of use of the atomizing core, but also increases the usage cost. Summary of the Invention [Problem to be solved by the invention]

[0004] The technical problem to be solved by the present invention is to provide a porous atomizing core capable of releasing negative ions and a manufacturing method thereof. [Means for solving the problem]

[0005] The technical solution adopted by the present invention to solve the technical problem is to provide a porous atomizing core capable of releasing negative ions, which comprises, as raw materials and their mass parts, 50-90 parts of tourmaline, 0-30 parts of ceramic powder, 10-30 parts of pore former, 0-30 parts of combustion improver, 0-35 parts of paraffin, and 0-2 parts of surfactant.

[0006] The ceramic powder includes at least one of negative ion powder, far infrared powder, attapulgite, feldspar, and zeolite.

[0007] Preferably, the tourmaline is a primary modified tourmaline.

[0008] Preferably, the primary modified tourmaline is obtained by the following modification method. That is, 100 parts of tourmaline is added to a cerium nitrate hydrate solution with a mass fraction of 1 to 10%, and then placed in a chromatography column for circulation and overloading for 2 to 5 hours. Next, the suspension after the overloading is stirred by magnetic force, and ammonia water with a mass fraction of 5 to 10% is slowly dropped. Then, when the pH value reaches 10, the dropping is stopped, pure water is added, and the mixture is stirred and washed several times, and the supernatant liquid is removed. This is dried in an oven at 70 to 90°C, and then placed in a sintering furnace and calcined at 500 to 600°C for 4 to 6 hours.

[0009] Preferably, the tourmaline is a second-order modified tourmaline.

[0010] Preferably, the second-order modified tourmaline is obtained by the following modification method: take 100 parts of first-order modified tourmaline and 200 parts of anhydrous ethanol, mix them together, Magnetic stirring Next, add 60 parts of butyl titanate and stir for 2-3 hours. After stirring is complete, remove the supernatant. Dry the mixture in an oven at 70-90℃, then place it in a sintering furnace and calcinate it at 450-550℃ for 3-4 hours.

[0011] Preferably, the primary modified tourmaline is obtained by the following modification method. That is, 100 parts of tourmaline is added to a cerium nitrate hydrate solution with a mass fraction of 1 to 10%, and then placed in a chromatography column for circulation and overloading for 2 to 5 hours. Next, the suspension after the overloading is stirred by magnetic force, and ammonia water with a mass fraction of 5 to 10% is slowly dropped. Then, when the pH value reaches 10, the dropping is stopped, pure water is added, and the mixture is stirred and washed several times, and the supernatant liquid is removed. This is dried in an oven at 70 to 90°C, and then placed in a sintering furnace and calcined at 500 to 600°C for 4 to 6 hours.

[0012] Preferably, the tourmaline has a particle size of 100-1500 mesh, and the ceramic powder has a particle size of 100-1500 mesh.

[0013] Preferably, the combustion improver is at least one of metal oxide and glass powder, has a particle size of 325 to 2000 mesh, and has a melting start temperature of 300 to 500°C.

[0014] Preferably, the pore-forming agent is at least one of wheat flour, PS microspheres, C powder and rice husk powder, and has a particle size of 80-1000 mesh.

[0015] Preferably, the paraffin is semi-refined or refined paraffin and has a melting point of 40 to 100°C.

[0016] Preferably, the surfactant is at least one of sorbitan fatty acid esters, polysorbates, stearic acid and oleic acid.

[0017] The present invention further provides a method for manufacturing a porous atomizing core capable of releasing negative ions, the method comprising the steps of:

[0018] S1: Mix the raw materials according to the weight parts and press to form a base material.

[0019] S2: The base material is placed in a sintering furnace and sintered by increasing the temperature to 600-800°C at a heating rate of 1-10°C / min. Effect of the Invention

[0020] The beneficial effects of the present invention are as follows: tourmaline is used as one of the raw materials, and its pyroelectric, piezoelectric, infrared radiation, negative oxygen ion emission and bioelectric properties are utilized to decompose and remove harmful gases in the atomizing liquid and air, thereby making the porous atomizing core environmentally friendly and with excellent atomizing effect, thereby satisfying people's pursuit of health products and extending the service life of the atomizing core.

[0021] The present invention will be further described below in combination with the drawings and examples. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is an SEM image of the secondarily modified tourmaline of the present invention. [Diagram 2] FIG. 2 is a SEM image of a porous atomizing core capable of releasing negative ions in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In order to make the technical features, objects and effects of the present invention more clearly understandable, specific embodiments of the present invention will be described in detail with reference to the drawings.

[0024] The porous atomizing core capable of releasing negative ions in the present invention contains, as raw materials and their mass parts, 50 to 90 parts of tourmaline, 0 to 30 parts of ceramic powder, 10 to 30 parts of a pore-forming agent, 0 to 30 parts of a combustion improver, 0 to 35 parts of paraffin, and 0 to 2 parts of a surfactant.

[0025] Tourmaline is a silicate mineral with a ring structure, and its special crystal structure has a permanent spontaneous polarization effect, which gives it pyroelectric, piezoelectric, infrared radiation, negative oxygen ion emission, and bioelectric properties. The far infrared rays generated by tourmaline can kill bacteria in the nebulizer liquid, promote blood circulation, and promote metabolism. In addition, the negative ions generated by tourmaline can ionize the nebulizer liquid to make it weakly alkaline, which further contributes to physical and mental health. In addition, the microcurrent generated by tourmaline is the same as the weak biocurrent in the human body, and can cause bioelectric phenomena in the human body.

[0026] Preferably, the tourmaline has a particle size of 100 to 1500 mesh.

[0027] Furthermore, in order to improve the emission performance of negative ions and far infrared rays in tourmaline, the tourmaline is modified to form a primary modified tourmaline or a secondary modified tourmaline.

[0028] Primary modified tourmaline is obtained by the following modification method. That is, 100 parts of tourmaline are added to an appropriate amount of cerium nitrate hydrate solution (cerium nitrate hydrate solution) with a mass fraction of 1 to 10%, mixed, and placed in a chromatography column for circulation and overloading for 2 to 5 hours. Next, the suspension that has completed overloading is stirred by magnetic force, and ammonia water with a mass fraction of 5 to 10% is slowly dropped. Then, when the pH value reaches 10, the dropping is stopped, pure water is added, and the mixture is stirred and washed several times (for example, twice), and the supernatant liquid is removed. This is dried in an oven at 70 to 90 ° C, and then placed in a sintering furnace and calcined at 500 to 600 ° C for 4 to 6 hours. The product obtained after calcination is primary modified tourmaline.

[0029] The above primary modified tourmaline can be modified again to obtain secondary modified tourmaline. The modification method is as follows: take 100 parts of primary modified tourmaline and 200 parts of anhydrous ethanol, mix them, and then Magnetic stirringThen, add 60 parts of butyl titanate and stir for 2-3 hours. After stirring, remove the supernatant liquid. Dry it in an oven at 70-90℃, then place it in a sintering furnace and calcinate it at 450-550℃ for 3-4 hours. The product obtained after calcination is the secondary modified tourmaline.

[0030] The SEM image of the secondary modified tourmaline is shown in Figure 1. From Figure 1, we can see that the surface of the tourmaline after the secondary modification is smooth. After the tourmaline is bonded with TiO2, many fine particles appear on the surface, which means that the modification result is favorable.

[0031] During the first modification, Ce (cerium) has two types of variable valence. Ce 3+ is Ce under light irradiation conditions. 4+ During the process of the change, electron-hole recombination occurs. However, due to the presence of electrostatic fields at both ends of tourmaline, the electrons involved in the recombination move due to the action of the electric field, reducing the probability of electron-hole recombination. As a result, a large amount of energy is stored on the surface of the tourmaline / Ce composite material, increasing the amount of negative oxygen ions released. In addition, during the secondary modification, the titanium dioxide produced has a photocatalytic effect, which not only improves the effect of the primary modification, but also promotes the emission of negative ions and far infrared rays from tourmaline when the electrons on the TiO2 surface absorb sufficient energy and leave when irradiated with light or ultraviolet rays.

[0032] The ceramic powder contains at least one of negative ion powder, far infrared powder, attapulgite, feldspar, and zeolite, and has a particle size of 100 to 1500 mesh. The feldspar is potassium feldspar and / or albite.

[0033] The combustion improver is at least one of metal oxide and glass powder, and has a particle size of 325 to 2000 mesh and a melting start temperature of 300 to 500° C. The metal oxide can be at least one of magnesium oxide, titanium dioxide, niobium oxide, etc.

[0034] The pore-forming agent is at least one of wheat flour, PS microspheres, C powder (carbon powder) and rice husk powder, and has a particle size of 80 to 1000 mesh.

[0035] Paraffin is semi-refined or refined paraffin, and has a melting point of 40 to 100°C.

[0036] The surfactant is at least one of sorbitan fatty acid ester (Span), polysorbate (Tween), stearic acid, and oleic acid.

[0037] The method for manufacturing a porous atomizing core capable of releasing negative ions in the present invention includes the following steps.

[0038] S1: Mix the raw materials according to the weight parts and press to form a base material.

[0039] As for the press molding, hot die casting may be used, or dry press molding may be used.

[0040] Furthermore, in the case of hot die casting, the content of the combustion improver in the raw material is preferably 10 to 30 parts, the content of the paraffin is preferably 15 to 35 parts, and the content of the surfactant is preferably 0.05 to 2 parts.

[0041] In the case of dry press molding, it is not necessary to add a combustion improver, paraffin, or surfactant to the raw material.

[0042] S2: The green body is placed in a sintering furnace, and the temperature is increased to 600-800°C at a heating rate of 1-10°C / min to sinter it, thereby obtaining a porous atomized core by a single sintering method.

[0043] As can be understood, the manufacturing method of the porous atomizing core capable of releasing negative ions in the present invention is not limited to the above-mentioned hot die casting or dry pressing, and any other methods for molding and manufacturing the atomizing core can be used.

[0044] The SEM image of the porous atomizing core capable of releasing negative ions in the present invention is shown in Figure 2. It can be seen from the figure that the atomizing core has many voids and the voids are uniform. The uniform voids can fully guarantee the function and effect of tourmaline and can improve the atomizing effect.

[0045] The present invention will now be further described with reference to specific examples.

[0046] Example 1 Each ingredient mass The parts were 80 parts of unmodified tourmaline, 20 parts of glass powder, 20 parts of wheat flour, 20 parts of paraffin, and 0.5 parts of oleic acid. After mixing the above raw materials, they were hot-die cast and sintered once at 600-800°C to form a porous atomizing core.

[0047] Example 2 The same procedure was followed as in Example 1, except that the tourmaline was changed to a primary modified tourmaline.

[0048] Example 3 The same procedure was followed as in Example 1, except that the tourmaline was changed to a second-order modified tourmaline.

[0049] Example 4 Each ingredient mass The parts were 80 parts of unmodified tourmaline, 20 parts of glass powder, 5 parts of negative ion powder, 20 parts of wheat flour, 20 parts of paraffin, and 0.5 parts of oleic acid. After mixing the above raw materials, hot die casting was performed and sintered once at 600 to 800 ° C to form a porous atomizing core.

[0050] Example 5 Each ingredient mass The mixture was dry press molded with 80 parts of secondary modified tourmaline, 5 parts of feldspar, 15 parts of attapulgite, and 20 parts of wheat flour, and sintered once at 600 to 800°C to form a porous atomization core.

[0051] Comparative Example 1 The same procedure as in Example 1 was repeated, except that the tourmaline in Example 1 was replaced with aluminum oxide.

[0052] The negative ion emission performance of the atomizing cores obtained in Examples 1 to 5 and Comparative Example 1 was measured. The negative ion content in solids and air was measured using a negative ion measuring device for solids COM-3010PRO and a negative ion measuring device for air COM-3200PRO II. The negative ions in air were measured using a 1m 3 The measurement was performed for 20 to 60 minutes in a closed space. The sample size of the atomization core was a circular plate with a thickness of 1 cm and a diameter of 10 cm. The measurement results are shown in Table 1.

[0053] [Table 1]

[0054] As can be seen from Table 1, in the present invention, by adding tourmaline, the atomizing core has the function of releasing negative ions, etc. Moreover, the effect of modified tourmaline is better, and the negative ion powder has the same effect.

[0055] The above description is merely an embodiment of the present invention, and does not limit the scope of the present invention. Any equivalent structure or equivalent flow modification made using the contents of the specification and drawings of the present invention, or direct or indirect operation in other related technical fields, are all included in the scope of protection of the present invention for the same reasons.

Claims

1. The raw materials and the mass parts thereof include 50 to 90 parts of tourmaline, 0 to 30 parts of ceramic powder, 10 to 30 parts of a pore former, 0 to 30 parts of a combustion improver, 0 to 35 parts of paraffin, and 0 to 2 parts of a surfactant; The ceramic powder includes at least one of a negative ion powder, a far infrared ray powder, an attapulgite, a feldspar, and a zeolite; The tourmaline is a primary modified tourmaline; The primary modified tourmaline is obtained by the following modification method: 100 parts of tourmaline is added to a cerium nitrate hydrate solution with a mass fraction of 1-10%, then placed in a chromatography column for circulating and overloading for 2-5 hours; the suspension after the overloading is stirred by magnetic force, and ammonia water with a mass fraction of 5-10% is slowly dropped into the suspension; when the pH value reaches 10, the dropping is stopped; pure water is added, the mixture is stirred and washed several times, and the supernatant liquid is removed; the mixture is dried in an oven at 70-90°C, and then placed in a sintering furnace for calcining at 500-600°C for 4-6 hours. This method for producing a porous atomizing core capable of releasing negative ions is characterized by being obtained by the following modification method.

2. The raw materials and the mass parts thereof include 50 to 90 parts of tourmaline, 0 to 30 parts of ceramic powder, 10 to 30 parts of a pore former, 0 to 30 parts of a combustion improver, 0 to 35 parts of paraffin, and 0 to 2 parts of a surfactant; The ceramic powder includes at least one of a negative ion powder, a far infrared ray powder, an attapulgite, a feldspar, and a zeolite; The tourmaline is a second-order modified tourmaline; The secondarily modified tourmaline is obtained by the following modification method: 100 parts of the first modified tourmaline and 200 parts of anhydrous ethanol are mixed and stirred by magnetic force, then 60 parts of butyl titanate are added and stirred for 2-3 hours, after stirring is completed, the supernatant liquid is removed, it is dried in an oven at 70-90°C, and then it is placed in a sintering furnace and calcined at 450-550°C for 3-4 hours. The primary modified tourmaline is obtained by the following modification method: 100 parts of tourmaline is added to a cerium nitrate hydrate solution with a mass fraction of 1-10%, then placed in a chromatography column for 2-5 hours of circulation and overloading; the suspension after the overloading is magnetically stirred, and ammonia water with a mass fraction of 5-10% is slowly dropped into the suspension; when the pH value reaches 10, the dropping is stopped; pure water is added, and the mixture is stirred and washed several times, and then the supernatant liquid is removed; the mixture is dried in an oven at 70-90°C, and then placed in a sintering furnace for calcination at 500-600°C for 4-6 hours. The method for producing a porous atomizing core capable of releasing negative ions is characterized by the above modification method.

3. The method for producing a porous atomizing core capable of releasing negative ions according to any one of claims 1 and 2, characterized in that the particle size of the tourmaline is 100 to 1500 mesh, and the particle size of the ceramic powder is 100 to 1500 mesh.

4. The combustion improver is at least one of metal oxide and glass powder, has a particle size of 325 to 2000 mesh, and has a melting start temperature of 300 to 500° C. The method for producing a porous atomizing core capable of releasing negative ions according to any one of claims 1 and 2, characterized in that the pore-forming agent is at least one of wheat flour, PS microspheres, C powder and rice husk powder, and has a particle size of 80 to 1000 mesh.

5. The paraffin is semi-refined or refined paraffin and has a melting point of 40 to 100° C.

3. The method for producing a porous atomizing core capable of releasing negative ions according to claim 1, wherein the surfactant is at least one of sorbitan fatty acid ester, polysorbate, stearic acid, and oleic acid.

6. S1: Mix each raw material according to the mass parts and press it to form a base material; S2: The method for manufacturing a porous atomizing core capable of releasing negative ions according to any one of claims 1 to 5, further comprising the steps of: placing the base material in a sintering furnace, and heating the base material to 600 to 800°C at a heating rate of 1 to 10°C / min to sinter the base material.

Citation Information

Patent Citations

  • Negative ion humidification porous ceramic and preparation method thereof

    CN105218147A

  • Modified tourmaline powder for ceramic glaze, anion ceramic glaze and preparation method

    CN105541410A

  • Porous ceramic and manufacturing method thereof

    CN109336561A

  • Porous ceramic material with adsorption and ion dissolution functions and manufacturing method thereof

    CN112408963A

  • Multifunctional composite ceramic filter element and preparation method thereof

    CN112592198A